Previous COVID-19 infection significantly reduces elastase levels in newly diagnosed pulmonary tuberculosis patients - Nancy Hilda Joseph; Alangudi Palaniappan Natarajan; Saravanan Natarajan; Chinnaiyan Ponnuraja; Madeshwaran A; Gunaparvathy I; Hemalatha P; Rajeshwari S; Lavanya Jayabal; Mahilmaran Ayyamperumal; Ramesh P. M.; Luke Elizabeth Hanna (Frontiers in Immunology, 2025)
IntroductionTuberculosis (TB) is considered a risk factor for severe COVID-19 disease and the quality of life of patients co-infected with COVID-19 and TB is significantly impacted due to the nature of these diseases. It is still unknown how our immune system will respond to both these pathogens in sequel. As it has been discovered that Neutrophil extracellular traps (NETs) result in caseating granulomas in TB and pathology in COVID-19, we conducted this work to determine the amounts of NET molecules in the bloodstream and to comprehend their function during TB and subsequent SARS-CoV-2 infection.MethodsWe recruited 43 healthy volunteers, 40 newly diagnosed pulmonary tuberculosis patients who were negative for SARS-CoV-2 IgG antibody and 18 newly diagnosed pulmonary tuberculosis patients who were positive for SARS-CoV-2 IgG.ResultsAlthough Citrullinated Histone H3 and myeloperoxidase, did not show any difference in their levels, the NET marker elastase had significantly reduced circulatory levels in the tuberculosis group with SARS-CoV IgG positivity compared to tuberculosis group without SARS-CoV-2 IgG positivity.DiscussionThe substantial decrease in elastase levels observed in the diabetic cohort of TB patients with SARS-CoV-2 IgG positivity is intriguing and needs large cohort studies in the future to understand the influence of diabetes in TB patients exposed to SARS-CoV-2.